Does Occupational Stress Play a Role in Forming Restrictionist Immigration Opinions?. Issue 4 (2nd October 2022) - Berg, Justin Allen
ABSTRACT: This study extends the labor market competition perspective of immigration attitudes by examining the influence of occupational stress and employer-sponsored stress management programs on native-born, full-time workers' opinions toward immigration levels. Binary logit and ordered logit models, with data from the 2018 General Social Survey, test the predictions of three occupational stress theories: job demands-control-support, effort-reward balance, and distributive justice. The results indicate that native-born, non-Hispanic white workers and native-born, Latino workers who are unable to develop their occupational skills on the job have greater odds of favoring reduced immigration. Job insecurity, lack of promotion opportunities, and poor intercolleague respect also negatively affect native-born, non-Hispanic white workers' immigration opinions, while having to expend greater physical effort and having less time to complete the work negatively affect native-born, Latino workers' immigration opinions. At the same time, native-born, non-Hispanic white workers who participate in stress management training have significantly greater odds of supporting increased immigration levels and significantly lower odds of desiring lower immigration levels. As immigration to the United States remains strong, understanding the social processes of native-born employee perceptions and the solutions to problematic intergroup relations may benefit individuals, businesses, and the economy.